Artemisinin conferred cytoprotection to human retinal pigment epithelial cells exposed to amiodarone-induced oxidative insult by activating the CaMKK2/AMPK/Nrf2 pathway - Chao Yang; Xia Zhao; Wenshu Zhou; Qin Li; Philip Lazarovici; Wenhua Zheng (Journal of Translational Medicine, 2024)
Abstract Background Ocular toxicity is a severe adverse effect that limits the chronic clinical use of the antiarrhythmic drug amiodarone. Here, we aimed to evaluate the cytoprotective effect of artemisinin and explore the potential signalling pathways in human retinal pigment epithelial (RPE) cell cultures. Methods D407 cell cultures were exposed to amiodarone and the impact of artemisinin was evaluated. The key parameters included lactate dehydrogenase (LDH) release, intracellular reactive oxygen species (ROS) generation, and the mitochondrial membrane potential (MMP). We also assessed the protein levels of cleaved caspase-3, cleaved poly (ADP-ribose) polymerase (PARP), phosphorylated adenosine monophosphate-activated protein kinase (AMPK)ɑ (p-AMPK), calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2), and nuclear factor erythroid 2-related factor 2 (Nrf2). Results Artemisinin reduced the cytotoxicity induced by amiodarone, as reflected by decreased LDH release, ROS generation, and MMP disruption. Additionally, artemisinin increased p-AMPK, CaMKK2, and Nrf2 protein levels. Inhibition of AMPK, CaMKK2, or Nrf2 abolished the cytoprotective effect of artemisinin. AMPK activation and Nrf2 knockdown further supported its protective role. Conclusions Artemisinin protected RPE cells from amiodarone-induced damage via the CaMKK2/AMPK/Nrf2 pathway. The in vivo experiments in mice confirmed its efficacy in preventing retinal injury caused by amiodarone. These results suggest that an artemisinin-based eye formulation could be repurposed for treating amiodarone-induced ocular toxicity.